2018
DOI: 10.1080/17445302.2018.1430200
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of residual ultimate strength of dented metallic pipes subjected to pure bending

Abstract: A dent is one of the main structural damages that may affect ultimate strength. In this paper, the residual ultimate strength of dented metallic pipes subjected to a bending moment is quantitatively investigated. The numerical model is developed accounting for the variation of the dent length (l d ), dent depth (d d ), dent width (w d ), dent rotation angle (θ d ) and dent location based on ABAQUS Python. The numerical model is validated by test results from a four-point bending test. Subsequently, a parametri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The value of curvature diagrams with the variation of the dent depth, length and width. Compared with the intact pipe, it is found that the occurrence of a particular dent affects its strength, Furthermore, as obtained from the former research by Cai et al (2018a), it is also observed from 485 Fig. 15 that both the dent depth (d d ) and length (l d ) have a considerable influence on the bending behavior, decreasing both the ultimate bending moment and critical curvature significantly.…”
Section: Simulation Results Of Dentmentioning
confidence: 61%
See 2 more Smart Citations
“…The value of curvature diagrams with the variation of the dent depth, length and width. Compared with the intact pipe, it is found that the occurrence of a particular dent affects its strength, Furthermore, as obtained from the former research by Cai et al (2018a), it is also observed from 485 Fig. 15 that both the dent depth (d d ) and length (l d ) have a considerable influence on the bending behavior, decreasing both the ultimate bending moment and critical curvature significantly.…”
Section: Simulation Results Of Dentmentioning
confidence: 61%
“…6. Here, the dented region has not been specially partitioned as in the former research (Cai et al, 2018a), instead, a general refined mesh strategy is assigned in this region. The mesh is largely refined in the damaged region in order to avoid the artificial bending moment, with the minimum mesh equal to 2 mm, i.e.…”
Section: Dented Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that quantification of damage effect cannot be done due to the limited number of specimens in the test. Other research is needed, as seen in the published papers by the authors [36,37].…”
Section: The Effect Of Dentmentioning
confidence: 99%
“…In the former research of the authors [1][2][3], a four-point bending test has been successfully carried out on metallic seamless pipes with different types of structural damage. Influential parameters such as materials, test boundaries and initial imperfections have been identified.…”
Section: Introductionmentioning
confidence: 99%